Analisis Kinerja Distributor Valve pada Sistem Pengereman Kereta Penumpang Berbasis Air Brake System - Windy Andaresta; Abri Andry Saresa Marbun; Agnes Manurung; Boby Sahat Maruli Malau (Nozel : Jurnal Pendididikan Teknik Mesin, 2026)
The braking system is a vital component in railway operations that plays an important role in ensuring travel safety. One of the main components in an air brake system is the distributor valve, which functions to regulate the distribution of air pressure to the brake cylinder. This study aims to analyze the performance of the distributor valve in a passenger train braking system based on an air brake system. The methods used include field observations, literature studies, and analysis of the working process and pressure response of the braking system. The results show that the distributor valve is capable of responding effectively to changes in brake pipe pressure, with a maximum pressure reaching 3.8 bar, thereby producing optimal braking force. In addition, the system demonstrates stability during both the braking and brake release processes in accordance with the working principles of the air brake system. Therefore, the performance of the distributor valve is considered to meet operational standards and plays an important role in maintaining the safety of the railway braking system.